2006
DOI: 10.1300/j200v04n02_01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of a Cognitive-Behavioral Intervention with Depressed Latinas

Abstract: A 12-session Cognitive-Behavioral Treatment (CBT) protocol for depression developed at San Francisco General Hospital was pilot tested with Latinas in New York City. Viability of the protocol and indication of treatment efficacy was sought as a rationale for more controlled investigation of the intervention on Latino urban populations in the Northeast. The pre-and post-treatment BDI scores for all five participants declined an average of 12 points (95% CI: [3, 21], p < 0.01). Given the lack of control group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…First, results may have been influenced by the short duration of the CBI treatment and the insufficient time for the cognitive-behavioral skills to be learned and applied to everyday life. Previous studies have shown that CBT was effective in improving treatment outcomes in 12 sessions (Cucciare, Sorrell, & Trafton, 2009;Gelman, López, & Foster, 2005;Gonzalez et al, 2010;Hinton et al, 2005;Organista, Muñoz, & González, 1994). Given that this study provided CBT over just 6 sessions and that other studies showed efficacy with CBT conducted over 12 sessions, results might suggest that the intervention may not have been long enough.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…First, results may have been influenced by the short duration of the CBI treatment and the insufficient time for the cognitive-behavioral skills to be learned and applied to everyday life. Previous studies have shown that CBT was effective in improving treatment outcomes in 12 sessions (Cucciare, Sorrell, & Trafton, 2009;Gelman, López, & Foster, 2005;Gonzalez et al, 2010;Hinton et al, 2005;Organista, Muñoz, & González, 1994). Given that this study provided CBT over just 6 sessions and that other studies showed efficacy with CBT conducted over 12 sessions, results might suggest that the intervention may not have been long enough.…”
Section: Discussionmentioning
confidence: 81%
“…In previous research, CBT was effective in improving adherence to self-care behaviors among individuals with type 2 diabetes (Christie & Wilson, 2005;Foreyt & Poston, 1999;Gonzalez et al, 2010;Lustman et al, 1998;Snoek & Skinner, 2002;Surwit et al, 2002). Research also showed that CBT was effective in treating psychological diagnoses such as depression, anxiety, and post-traumatic stress disorder among Asian Americans and Pacific Islanders (Dai et al, 1999;Gelman et al, 2005;Voss Horrell, 2008).…”
Section: Other Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Of the 15 studies, nine were quantitative [ 51 - 54 , 56 , 57 , 60 , 63 , 64 ], five employed mixed methods [ 50 , 55 , 58 , 59 , 62 ] and one case study presented qualitative data [ 61 ]. Nine studies reported on culturally sensitive/culturally adapted psychological treatments (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There was a underrepresentation of men in the included studies; five of 15 studies specifically recruited only women [ 51 , 52 , 55 , 58 , 59 ], one study reported having no male participants [ 57 ] and two case studies did not describe gender as an inclusion criteria but only included female participants [ 50 , 61 ]. Women, on average, represented 81.2% of the study cohorts, though none of the remaining studies sought to exclude males.…”
Section: Resultsmentioning
confidence: 99%